EFFICACY OF INTRA OPERATIVE USE OF TRIAMCINOLONE IN LUMBAR DISCECTOMY - Asim Ishfaq (Army Medical College Rawalpindi, 2020)
Objective: To evaluate the effect of epidural application of triamcinolone during lumbar discectomy on postoperative pain relief.